Animal growth in random environments: estimation with several paths - Filipe, Patrícia A. (2008)
Refereed scientific paper on stochastic differential equation models of individual animal growth (from birth to maturity) in random environments with estimation methods for several trajectories (several animals). The paper is in press in the Bulletin of ISI containing the Proceedings of the 56th Session of the ISI (2007). An electronic version is available.